Bacteria in Agrobiology: Plant Growth Responses - Maheshwari, Dinesh K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
The future of agriculture strongly depends on our ability to enhance productivity without sacrificing long-term production potential. An ecologically and economically sustainable strategy is the application of microorganisms, such as the diverse bacterial species of plant growth promoting bacteria (PGPB). The use of these bio-resources for the enhancement of crop productivity is gaining worldwide importance. (3z(BBacteria in Agrobiology: Plant Growth Responses(3y (Bdescribes the application of various bacteria in plant growth promotion and protection, including symbiotic, free living, rhizospheric, endophytic, methylotrophic, diazotrophic and filamentous species.s
Passaglia: Genetic and Phenotypic Diversity of Plant-Growth Promoting Bacilli -- Bacon: Bacillus mojavensis: its Endophytic Nature, the Surfactins and their Role in the Plant Response -- Borris: Increasing use of Plant-Associated Bacillus Strains as Biofertilizers and Biocontrol Agents in Agriculture -- Sakthivel: Antimicrobial Metabolites by Fluorescent Pseudomonads for Biocontrol Applications -- Andres: Role of Pseudomonas aurantiaca in Crop Improvement -- Reis: What is Expected from the Genus Azospirillum as Plant Growth-Promoting Bacteria?- Katsy: Plasmid Plasticity in the Plant-Associated Bacteria of the Genus Azospirillum -- Saraf: Enterobacter species: Role in Plant Growth Promotion -- Doty: Nitrogen-Fixing Endophytes for Improved Plant Growth -- Shimizu: Endophytic actinomycetes as Biocontrol Agents -- Tsavkelova: Bacteria Associated with Roots of Greenhouse Orchids -- Sa: Diversity and Beneficial Interactions among Methylobacterium and Plants -- Strap: Actinobacteria-Plant Interactions, A boon to Agriculture -- Sa: Insect Gut Bacteria: An Unexplored Niche for Plant Growth Promotion -- Tofazzal: Biological Control of Plant Diseases by Lysobacter Species.
Keywords: Life sciences; Biotechnology; Microbiology; Agriculture; Bacteriology; Plant physiology; Life Sciences; Bacteriology; Agriculture; Plant Physiology; Applied Microbiology; Biotechnology